2018
DOI: 10.1111/jgs.15276
|View full text |Cite
|
Sign up to set email alerts
|

Should Structured Exercise Be Promoted As a Model of Care? Dissemination of the Department of Veterans Affairs Gerofit Program

Abstract: Exercise provides a wide range of health-promoting benefits, but support is limited for clinical programs that use exercise as a means of health promotion. This stands in contrast to restorative or rehabilitative exercise, which is considered an essential medical service. We propose that there is a place for ongoing, structured wellness and health promotion programs, with exercise as the primary therapeutic focus. Such programs have long-lasting health benefits, are easily implementable, and are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…The Gerofit facility-based program is offered at 17 VA medical centers across the United States and is described in full elsewhere (Morey et al, 2018). The program is standardized for delivery across sites and provides individually tailored guidance for older adults' participation.…”
Section: Methodsmentioning
confidence: 99%
“…The Gerofit facility-based program is offered at 17 VA medical centers across the United States and is described in full elsewhere (Morey et al, 2018). The program is standardized for delivery across sites and provides individually tailored guidance for older adults' participation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is likely that, due to this high burden of comorbid conditions, many of these veterans would also struggle with exercise participation and compliance to a highly structured, progressive program, especially without clinical supervision. While we did not examine adherence or attendance in this current analysis, in our previous study, we reported that 53% of veterans were still active in the program after 3 months, and 42% after 6 months (Morey et al, 2018). This suggests that long-term participation in Gerofit is feasible.…”
Section: Discussionmentioning
confidence: 76%
“…We have previously published on the implementation of Gerofit across six sites: Baltimore, MD; Canandaigua, NY; Los Angeles, CA; Durham, NC; Salem, VA; and Honolulu, HI (Morey et al, 2018). For this secondary analysis, veterans enrolled into the Gerofit clinical demonstration program from these VA medical center's catchment areas prior to September 1, 2016, with complete baseline, 3-and 6-month mobility assessments were included in the analysis.…”
Section: Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations